Fabrication of flexible, binder-free, and self-standing nickel cobalt double hydroxide/graphene films for advanced alkaline batteries. (1st October 2022) - Huang, Longjun; Yao, Huan; Meng, Lijun; Dong, Wenju; Li, Luping; Liu, Yuxiu; Ji, Xu; Cheng, Shuang
Highlights: Flexible and lightweight NiCo-DH/GNP@rGO films are prepared via a simple dry pressing process. The film can deliver a high specific capacity of 213 mAh g-1 with good durability as cathode in alkaline solution. Using Zn foil as anode, a discharge voltage of 1.6 V can be accomplished for a full cell. Abstract: Rechargeable alkaline Ni-Zn batteries possess high promising in large-scale energy storage systems, and wearable flexible devices due to their low cost, high safety, and high energy density compared with other aqueous batteries. However, the traditional preparation method together with the use of bulky Ni mesh current collector has limited their applications. Herein, a simple dry pressing process without the using of any organic solvents is developed to prepare Binder-free, flexible, and lightweight Nickel Cobalt double hydroxide (NiCo-DH) based films, NiCo-DH/GNP@rGO, where NiCo-DH is prepared as active material, graphene nanoplatelets powder (GNP) is used as both conductive and supporting frame, and reduced graphene oxide (rGO) is coated as protective layer of the films. Areal mass of the flexible film is only about 4.2 mg cm −2, and mass loading of NiCo-DH is about 33%. In a three-electrode system, the NiCo-DH/GNP@rGO delivers a high specific capacity of 213 mAh g −1, and outstanding cycling performance (88.8% capacity retention after 1000 cycles' running at 1 A g −1 ). Assembled into a full cell using Zn foil as anode, a discharge voltage of 1.6 V is realized. The flexible films prepared here exhibit a promising application prospect in portable and wearable electronic devices.